Strategically Aligning Additive Manufacturing Supply Chains for Sustainability and Effectiveness. Issue 10 (2019) - Feldmann, Carsten; Delke, Vincent; Wasserman, Michael E.
Abstract: This paper builds on a previously developed framework that integrates additive manufacturing, life-cycle analysis, and value creation (Feldmann & Kirsch, 2019) by exploring conditions related to the life-cycle approach that would require alignment among suppliers, additive manufacturing firms, and customers. This extension creates a bridge to aid the implementation of taking a sustainability approach to additive manufacturing. In order to develop this extension, we distinguish between direct/indirect customers and internal/external customers and then create a matrix of incentives and cognitive frames that we believe will help companies interested in large-scale AM improve both the speed and the effectiveness of AM adoption. We provide an organizing framework that managers can use to create a supply chain that is aligned around closed-loop principles that will help speed adoption and move closer to sustainable goals that exist for AM technologies. These include reduced raw material use, reduced scrap and material overage, reduced rework, and lower transportation costs. The goal is to attain often-conflicting goals of lower long-term costs and decreased environmental footprint. Using our extension, we believe we can provide a useful framework to help managers implementing advanced manufacturing technologies to achieve lower costs and greater environmental sustainability by creating a common supply chain framework around customized, on-demand products.